2019
DOI: 10.1186/s12887-019-1558-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency and its association with metabolic derangements among children with obesity

Abstract: Background It is known that obesity is associated with vitamin D deficiency and observational studies have shown vitamin D deficiency to be linked with the development of type 2 diabetes. There are no comprehensive data regarding vitamin D deficiency in children with obesity in Sri Lanka and the objective of the study was to assess the prevalence of Vitamin D deficiency and its association with metabolic derangements among children with obesity. Methodology Two hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…In the present study, as several authors have described [21,27,[34][35][36], we found a significant inverse association between serum 25(OH)D concentrations and serum insulin and HOMA-IR. Observational studies have detected that lower 25(OH)D levels are associated with a higher prevalence of impaired glucose tolerance or diabetes type 2 [37][38][39].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, as several authors have described [21,27,[34][35][36], we found a significant inverse association between serum 25(OH)D concentrations and serum insulin and HOMA-IR. Observational studies have detected that lower 25(OH)D levels are associated with a higher prevalence of impaired glucose tolerance or diabetes type 2 [37][38][39].…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, several observational studies have revealed an inverse relationship between 25(OH)D levels and BMI in children with obesity [8,27,41]. However, as we observed in this study, other authors have not found such an association [21,42]. We found an inverse correlation of serum 25(OH)D concentrations with different anthropometric and biochemical measurements that are specific of adiposity, such as body fat percentage, fat mass index, and leptin.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…From previous studies, less vitamin D intake has a strong connection with obesity and diabetes . And the prevalence of vitamin D deficiency was very high among obese children . In a word, vitamin D deficiency is a risk factor of CRC, and it also has an influence on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques allows to recover the internal structure of on-shell particles from scattering of off-shell ones [7]. In the future, this gap may be bridged by the tagged DIS experiment at the upgraded Jefferson Laboratory (JLab 12) [8], and possibly kaon as well.…”
Section: Introductionmentioning
confidence: 99%